MANAJEMEN PEMASARAN INTERNAL DALAM MENINGKATKAN KEPUASAN DAN RETENSI SISWA - Edison, Edison (UNISAN JURNAL, 2024)
This study aims to examine the role of internal marketing management in enhancing student satisfaction and retention in educational institutions. Internal marketing is considered a crucial strategy that involves all organizational components, especially teaching and administrative staff, in creating a conducive learning environment, providing quality services, and maintaining effective communication with students. This research employs a descriptive qualitative approach with a literature review as the primary data source, including scientific journals, reference books, and institutional documents related to marketing management and customer satisfaction in the context of education. The findings indicate that when internal marketing strategies are consistently implemented—through teacher training, open internal communication, and the establishment of a service-oriented culture—they directly contribute to increased student satisfaction. This satisfaction leads to higher student retention, reflected in students' willingness to remain at the institution and recommend it to others. Therefore, educational institutions need to integrate internal marketing strategies as a fundamental part of their efforts to continuously improve the quality of educational services.